Skeppsbron ReLinked : a site specific development proposal of a historical quay - Kowalik, Konrad (SLU/Dept. of Urban and Rural Development, 2019)
Traffic routes and parked vehicles are frequently directed to quays. This urban pattern disrupt and depopulate the unique interface of the city and sea. Research unanimously confirms the causality between new roads and new traffic. The current planning policies point out; “If Stockholm’s traffic system is to work effectively, total volumes of traffic must be reduced, particularly car traffic”. Despite this, traffic flows are planned to be canalized along Stockholm’s most central and historic waterfronts - Skeppsbron.